Pengembangan Sains dan Perempuan Potret Semangat Ajaran Islam - Suryadi, Suryadi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
In the current phase of modernity, according to observation, the condition of women is still positioned as a subordinate being and is only for domestic